2021
DOI: 10.1016/j.neuron.2021.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendroglial ring finger protein Rnf43 is an essential injury-specific regulator of oligodendrocyte maturation

Abstract: Oligodendroglial ring finger protein Rnf43 is an essential injury-specific regulator of oligodendrocyte maturation Graphical abstract Highlights d RNF43 marks activated OPCs in human white matter injury d Rnf43 is required for OPC differentiation in injury, not in development d Rnf43 inhibits the Wnt pathway by regulating Fzd1 surface presentation on OPCs d Pharmacological inhibition of Fzd1 promotes OPC differentiation during remyelination

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 41 publications
4
29
0
Order By: Relevance
“…We further con rmed the hyperactivation of Wnt/β-catenin pathway in the OPCs, from the hippocampus of schizophrenia patients, by detecting an increased immunoreactivity of Wnt downstream gene RNF43 (181.4 ± 30.5% increase, Figure 6G-H). This is consistent with a recent nding that upregulation of RNF43 speci cally in OPCs correlates with hyperactivated Wnt-signaling in injuries 32,33 . In this regard, we postulate that the DISC1-Δ3 in OPCs mediates a 'gain-of-function' to promote the hyperactivity of the Wnt/β-catenin signaling pathway in schizophrenia brains.…”
Section: Hyperactivity Of Wnt/β-catenin Pathway In Opcs From Schizoph...supporting
confidence: 93%
See 1 more Smart Citation
“…We further con rmed the hyperactivation of Wnt/β-catenin pathway in the OPCs, from the hippocampus of schizophrenia patients, by detecting an increased immunoreactivity of Wnt downstream gene RNF43 (181.4 ± 30.5% increase, Figure 6G-H). This is consistent with a recent nding that upregulation of RNF43 speci cally in OPCs correlates with hyperactivated Wnt-signaling in injuries 32,33 . In this regard, we postulate that the DISC1-Δ3 in OPCs mediates a 'gain-of-function' to promote the hyperactivity of the Wnt/β-catenin signaling pathway in schizophrenia brains.…”
Section: Hyperactivity Of Wnt/β-catenin Pathway In Opcs From Schizoph...supporting
confidence: 93%
“…Our study further corroborates the multi-functional role of OPCs in the central nervous system (CNS). In other neurological disorders, such as multiple sclerosis, hypoxic-ischemic encephalopathy, and psychiatric diseases, OPCs not only contribute to aberrant myelin formation 33,51 , but are also involved in the regulation of blood-brain barrier integrity 36 , CNS immune regulation 53,54 and the behavioral outcomes 55,56 . In the present study, we generated a novel transgenic mouse strain to model the heterozygous DISC1 exon 3 splicing in patients with schizophrenia, and provided new evidence that such manipulation of DISC1 gene transcription exclusively in OPCs causes OPC hypertrophy, disrupts the formation of vGLUT1 + excitatory synapses, and initiate schizophrenia-like symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The g-ratio, given by the ratio of axon diameter to the summed diameter of axon and its surrounding myelin sheath, is an indicator of the degree of myelination in myelinated axons. A smaller g-ratio indicates a higher degree of myelination ( Buckley, et al 2010 ; Niu, et al 2021 ). A plot of g-ratios against axon diameters revealed that axons with larger diameters possessed significantly thicker myelination (i.e., smaller g-ratios) in the CC region of surface fish compared with cavefish ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…All human HIE tissue was collected with informed consent and in accordance with guidelines established by UCSF Committee on Human Research (H11170-19113-07) as previously described 111 . Immediately after procurement, all brains were immersed in PBS with 4% paraformaldehyde for 3 d. On day 3, the brain was cut in the coronal plane at the level of the mammillary body and immersed in fresh 4% paraformaldehyde and PBS for an additional 3 d. After fixation, all tissue samples were equilibrated in PBS with 30% sucrose for at least 2 d. After sucrose equilibration, tissue was placed into molds and embedded with optimal cutting temperature medium for 30 min at room temperature followed by freezing in dry ice–chilled ethanol.…”
Section: Methodsmentioning
confidence: 99%